Intelligent Interactive Technologies and Multimedia Second International Conference, IITM 2013, Allahabad, India, March 9-11, 2013. Proceedings - Agrawal, Anupam.; Agrawal, Anupam.; Tripathi, R.C.; Tripathi, R.C.; Do, Ellen Yi-Luen.; Do, Ellen Yi-Luen.; Tiwari, M. D.; Tiwari, M. D. (Communications in Computer and Information Science,, 2013)
This book constitutes the refereed proceedings of the Second International Conference on Intelligent Interactive Technologies and Multimedia, IITM 2013, held in Allahabad, India, in March 2013. The 15 revised full papers and the 12 revised short papers were carefully reviewed and selected from more than 90 submissions. The papers present the latest research and development in the areas of intelligent interactive technologies, human-computer interaction and multimedia.